Effects of saliva on starch-thickened drinks with acidic and neutral pH - Hanson, Ben; Cox, Ben; Kaliviotis, Efstathios; Smith, Christina H. (My University, 2012)
Powdered maize starch thickeners are used to modify drink consistency in the clinical management of dysphagia. Amylase is a digestive enzyme found in saliva which breaks down starch. This action is dependent on pH, which varies in practice depending on the particular drink. This study measured the effects of human saliva on the viscosity of drinks thickened with a widely used starch-based thickener. Experiments simulated a possible clinical scenario whereby saliva enters a cup and contaminates a drink. Citric acid (E330) was added to water to produce a controlled range of pH from 3.0 to 7.0, and several commercially available drinks with naturally low pH were investigated. When saliva was added to thickened water, viscosity was reduced to less than 1% of its original value after 10-15 min. However, lowering pH systematically slowed the reduction in viscosity attributable to saliva. At pH 3.5 and below, saliva was found to have no significant effect on viscosity. The pH of drinks in this study ranged from 2.6 for Coca Cola to 6.2 for black coffee. Again, low pH slowed the effect of saliva. For many popular drinks, having pH of 3.6 or less, viscosity was not significantly affected by the addition of saliva.
Keywords: Amylase; Deglutition; Deglutition disorders; pH; Rheology; Saliva; Starch; Thickener; Viscosity